PROGNOSTIC SIGNIFICANCE OF DETERMINING LEVELS OF MARKERS OF INFLAMMATION AND VON WILLEBRAND FACTOR IN ASSESSING THE RISK OF CORONARY HEART DISEASE - Voznyuk, L.; Pivtirak, E.; Semenenko, S. (World of Medicine and Biology, 2012)
FV level in the blood is pathophysiologic, clinically verified marker of endothelial dysfunction, which allows to evaluate the presence and severity of violations of the functional state of endothelium in coronary artery disease with a high degree of accuracy and time to appoint, monitor and adjust treatment aimed at restoring the damaged functional activity of endothelial cells in patients with this pathology.